Selecting appropriate bedding to reduce locomotion problems in broilers - ICL Almeida Paz; RG Garcia; R Bernardi; IA Nääs; FR Caldara; LW Freitas; LO Seno; VMOS Ferreira; DF Pereira; F Cavichiolo (Brazilian Journal of Poultry Science, 2010)
Two experiments were carried out at the Poultry Sector of the School of Agrarian Sciences of the Federal University of Grande Dourados to evaluate the incidence of leg problems in broilers reared on two distinct types of bedding material: rice husks or wood shavings, both new and reused. In both trials, a randomized experimental design was applied in factorial arrangement (2 x 2 x 2) using two genetic strains (Cobb® or Ross®); two sexes (male or female), and two litter materials (rice husks or wood shavings). In each trial 1080 one day pullets were reared equally divided in the treatments. The birds were placed in 4.5 m² boxes at a density of 10 birds m-2. All birds were fed diets with equal nutritional density, and water was offered ad libitum. Feeds were divided in three phases: starter diet (1 - 21 days), grower diet (22 - 35 days), and finisher diet (36 - 45 days). On day 45, fifty birds were randomly selected in each experiment to evaluate flock leg problems. The following parameters were analyzed: gait score, incidence of valgus and varus disorder, footpad dermatitis, femoral degeneration, tibial dyschondroplasia, and spondylolisthesis. Ambient temperature during rearing and litter caking and moisture content were recorded in four boxes per treatment. The analytical hierarchy process was used to organize the data into specific criteria. Several criteria, related to the attributes that were determinant according to the statistical analysis, were chosen in order to provide the best input to the process. Results indicated that new wood-shavings bedding was the most appropriate bedding to prevent locomotion problems, followed by new rice husks, reused wood shavings, and reused rice husks. However, when leg problems were associated to sex and genetic strain, male Ross birds strain presented less problems when reared on new rice husks, followed by new wood shavings